Effect of Plant Spacing and Leaf Clipping on Growth and Yield of Rice - Rahman, M L; Mim, S A; Ria, O A; Sabiha, U K; Alam, M M (Bangladesh Agronomy Journal, 2025)
Leaf cutting and spacing plays pivotal role in growth, yield and yield attributing parameters in rice cultivation by reducing different environmental stresses. To assess the effect of leaf cutting and spacing on plant growth and yield, an experiment was conducted with BRRI released Aman var. BRRI dhan62. The experiment consisted of two factors where spacing for the experiment were S1= 30 × 15 cm2, S2= 30 × 20 cm2, S3= 30 × 25 cm2 and the leaf cutting were T0= No leaf cutting, T1= Cutting of 1st basal leaf, T2= Cutting of 2nd basal leaf, T3= Cutting of 3rd basal leaf. The experiment was conducted with Randomized Complete Block Design (RCBD) with 4 replications. Results revealed that there was statistically no change in plant height, flag leaf width and length, panicle length, 1000-grain weight, filled grain panicle−1, and straw yield hill−1 at different spacing, leaf cutting, and their combination treatments. Regarding growth and yield parameters, the highest number of effective tillers hill−1 was found in combination T1 × S3, which was 50% greater compared to control plants. Total tillers hill−1 was found higher in combination T3 × S3, which was 39% higher than the control plants. Unfilled grain panicle−1 was found higher in combination T0 × S1, which was 75% higher than the lowest unfilled grain in T0 × S2, this indicates that even a minimal change in spacing can significantly impact yield attributes. Harvest index (HI) was found greater in combination T2 × S2, which was 15% higher than the control. The lowest number of filled grain panicle−1 was spotted at T3 × S3 combination indicating that with higher leaf cutting and spacing filled grain number reduced. The growth, yield and yield-contributing parameters showed the best results in 30 × 20 cm2 spacing in combination with cutting of 2nd basal leaf. Bangladesh Agron. J. 2024, 27(2): 70-77